Effect of BMITFSI to the electrical properties of chitosan/methylcellulose based polymer electrolyte - Misenan M.S.M.; Shaffie A.H.; Azwani Sofia Ahmad Khiar (American Institute of Physics Inc., 2024)
Indexed by WOS/ Scopus